Adult height, coronary heart disease and stroke: a multi-locus Mendelian randomization meta-analysis. (15th May 2015) - Nüesch, Eveline; Dale, Caroline; Palmer, Tom M; White, Jon; Keating, Brendan J; van Iperen, Erik PA; Goel, Anuj; Padmanabhan, Sandosh; Asselbergs, Folkert W; ,; Verschuren, WM; Wijmenga, C; et al.
Abstract: Background: We investigated causal effect of completed growth, measured by adult height, on coronary heart disease (CHD), stroke and cardiovascular traits, using instrumental variable (IV) Mendelian randomization meta-analysis. Methods: We developed an allele score based on 69 single nucleotide polymorphisms (SNPs) associated with adult height, identified by the IBCCardioChip, and used it for IV analysis against cardiovascular risk factors and events in 21 studies and 60 028 participants. IV analysis on CHD was supplemented by summary data from 180 height-SNPs from the GIANT consortium and their corresponding CHD estimates derived from CARDIoGRAMplusC4D. Results: IV estimates from IBCCardioChip and GIANT-CARDIoGRAMplusC4D showed that a 6.5-cm increase in height reduced the odds of CHD by 10% [odds ratios 0.90; 95% confidence intervals (CIs): 0.78 to 1.03 and 0.85 to 0.95, respectively], which agrees with the estimate from the Emerging Risk Factors Collaboration (hazard ratio 0.93; 95% CI: 0.91 to 0.94). IV analysis revealed no association with stroke (odds ratio 0.97; 95% CI: 0.79 to 1.19). IV analysis showed that a 6.5-cm increase in height resulted in lower levels of body mass index ( P  < 0.001), triglycerides ( P  < 0.001), non high-density (non-HDL) cholesterol ( P  < 0.001), C-reactive protein ( P  = 0.042), and systolic blood pressure ( P  = 0.064) and higher levels of forced expiratory volume in 1 s and forced vital capacity ( P  < 0.001 for both). Conclusions: Taller individuals have a lower risk of CHD with potential explanations being that taller people have a better lung function and lower levels of body mass index, cholesterol and blood pressure.